Anaphylaxis Triggered by Benzyl Benzoate in a Preparation of Depot Testosterone Undecanoate - Gregory S. Y. Ong; Colin P. Somerville; Timothy W. Jones; John P. Walsh (Case Reports in Medicine)
We report the first case of an anaphylactic reaction to Reandron 1000 (depot testosterone undecanoate with a castor oil and benzyl benzoate vehicle). While considered to have a favourable safety profile, serious complications such as oil embolism and anaphylaxis can occur. In our patient, skin testing identified benzyl benzoate to be the trigger, with no reaction to castor oil or testosterone undecanoate components. As benzyl benzoate exists in multiple pharmaceuticals, foods, and cosmetics, individual components of pharmaceuticals should be tested when investigating drug allergies. Doctors should be alert to the potential for serious reactions to any of the components of Reandron 1000.